2015
DOI: 10.1038/bjc.2015.82
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and relevance of QTc-interval prolongation caused by tyrosine kinase inhibitors

Abstract: Background:Tyrosine kinase inhibitors (TKIs) are associated with prolongation of the QTc interval on the electrocardiogram (ECG). The QTc-interval prolongation increases the risk of life-threatening arrhythmias. However, studies evaluating the effects of TKIs on QTc intervals are limited and only consist of small patient numbers.Methods:In this multicentre trial in four centres in the Netherlands and Italy we screened all patients who were treated with any TKI. To evaluate the effects of TKIs on the QTc interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 22 publications
2
59
1
2
Order By: Relevance
“…Erlotinib was predicted to have a high probability of inducing arrhythmia and myocardial infarction by the combined classifiers. In support of our model, recent studies reported that erlotinib induced QTc interval in patients 57 and CV damage in rat model. 58 In addition, an increasing number of clinical case reports of acute myocardial infarction following treatment by erlotinib in cancer patients also were reported.…”
Section: Resultssupporting
confidence: 88%
“…Erlotinib was predicted to have a high probability of inducing arrhythmia and myocardial infarction by the combined classifiers. In support of our model, recent studies reported that erlotinib induced QTc interval in patients 57 and CV damage in rat model. 58 In addition, an increasing number of clinical case reports of acute myocardial infarction following treatment by erlotinib in cancer patients also were reported.…”
Section: Resultssupporting
confidence: 88%
“…At baseline measurement, QTc intervals were significantly longer in females than in males (QTcfemales=404 ms vs QTcmales=399 ms, P=0.027) as expected. A statistically significant increase was observed in the individual treated with sunitinib, vemurafenib, sorafenib, imatinib, and erlotinib (median 0394;QTc ranging from +7 to +24 ms, P<0.004) 96 . Especially, patients treated with vemurafenib were at increased risk of developing a QTc of greater than or equal to 470 ms, a threshold associated with an increased risk for arrhythmias 96 .…”
Section: Multi-targeted Tyrosine Kinase Inhibitorsmentioning
confidence: 91%
“…Recently, a retrospective analysis was carried out on the multi-targeted tyrosine kinases. In this multicenter clinical trial four centers in the Netherlands and Italy screened patients who were treated with erlotinib, gefitinib, imatinib, lapatinib, pazopanib, sorafenib, sunitinib, or vemurafenib 96 . A total of 363 patients were eligible for the analyses.…”
Section: Multi-targeted Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…Planning for dose escalation has been considered for their clinical use, as many malignancies are thought to be caused by an aberrant tyrosine kinase function [1][2][3]. However, some TKIs have been reported to cause a significant prolongation of the electrocardiographic QTc interval when used to treat patients with advanced carcinoma [4]. Various agents and conditions that cause 2 of 13 prolongation of the QTc interval may predispose an individual to tosade de pointes tachyarrhythmia, which may result in syncope or sudden death [5,6].…”
Section: Introductionmentioning
confidence: 99%